Characterization of 2 Different Prothrombin Complex Concentrates by Different Hemostatic Assays in an In Vitro Hemodilution Model. (18th August 2022) - Infanger, Lukas; Hirschmann, Jörg; Schaden, Eva; Ulbing, Stefan; Pesce, Marco-Valerio; Scharner, Vincenz; Gratz, Johannes
Abstract : BACKGROUND: Viscoelastically guided coagulation factor concentrate-based algorithms for the treatment of trauma-induced coagulopathy include the administration of prothrombin complex concentrates (PCCs). However, the exact role of PCC preparations in this context is a matter of debate. Particularly, the ideal diagnostic trigger for their administration and potential differences between heparin-containing and heparin-free preparations remain unclear. We investigated the hypothesis that 2 different PCCs might have distinct influences on in vitro blood coagulation. METHODS: We conducted a direct comparison of 2 commercially available PCC preparations (the heparin-containing Beriplex P/N and the heparin-free Cofact) in an in vitro hemodilution model. Sole fibrinogen substitution served as the control group. To characterize the hemostatic changes, we utilized conventional coagulation tests, a thrombin generation assay (TGA), and 2 different viscoelastic hemostatic assays (VHAs; ROTEM delta and ClotPro). RESULTS: Irrespective of the diagnostic assay used, no significant differences between the 2 PCC groups were observed. Fibrinogen levels remained stable from the baseline throughout every dilution level. The control group already showed an increased endogenous thrombin potential (ETP; nM·L −1 ·min − 1 ) at all dilution levels compared to baseline (baseline, 2829.4 (432.8); 40% dilution, 4211.7 (391.6); 60% dilution, 4290.9 (300.8); 80% dilution, 3861.4 (303.5); all P < .001). Spiking with both PCC preparations led to a further-pronounced thrombin elevation in comparison to the control group (ETP at 40% dilution, PCC1: 4913.3 [370.2], PCC2: 4988.1 [265.7]; 60% dilution, PCC1: 5174.5 [234.7], PCC2: 5390.4 [334.9]; 80% dilution, PCC1: 5253.8 [357.9], PCC2: 5392.6 [313.4]; all P < .001). Conventional coagulation tests did not mirror the TGA results. Despite increased thrombin generation, prothrombin time was significantly prolonged at all dilution levels for the control group, and both PCC groups exhibited significant prolongations at the 60% and 80% dilution levels (all P < .001) compared to baseline. Similarly, VHA did not depict the thrombin elevation. Furthermore, descriptive analyses revealed relevant differences between the 2 VHA devices, particularly at baseline. CONCLUSIONS: Both PCC preparations (ie, irrespective of heparin content) induced significant elevation of thrombin generation, which was not depicted by conventional coagulation tests or VHA. Our in vitro results suggest that diagnostic assays routinely used to guide PCC administration might not adequately reflect thrombin generation in bleeding patients.